Proximity-Induced Superconductivity and Quantum Interference in Topological Crystalline Insulator SnTe Thin-Film Devices - Klett, Robin; Schonle, Joachim; Becker, Andreas; Dyck, Denis; Borisov, Kiril; Rott, Karsten; Ramermann, Daniela; Bueker, Bjoern; Haskenhoff, Jan; Krieft, Jan; Huebner, Torsten; Reimer, Oliver; et al. (Nano Letters, 2018)
Topological crystalline insulators represent a new state of matter, in which the electronic transport is governed by mirror-symmetry protected Dirac surface states. Due to the helical spin-polarization of these surface states, the proximity of topological crystalline matter to a nearby superconductor is predicted to induce unconventional superconductivity and, thus, to host Majorana physics. We report on the preparation and characterization of Nb-based superconducting quantum interference devices patterned on top of topological crystalline insulator SnTe thin films. The SnTe films show weak anti-localization, and the weak links of the superconducting quantum interference devices (SQUID) exhibit fully gapped proximity-induced superconductivity. Both properties give a coinciding coherence length of 120 nm. The SQUID oscillations induced by a magnetic field show 2π periodicity, possibly dominated by the bulk conductivity.
CRIS-Team Scopus Importer:2022-04-14
Keywords: mesoscopic devices; superconductivity; Thin films; topological insulator